Service preferences among postpartum women (non-)affected by different types of intimate partner violence: insights from the cross-sectional study INVITE - Laura M. Hausmann; Lara Seefeld; Amera Mojahed; Judith T. Mack; Susan Garthus-Niegel; Julia Schellong (BMC Public Health)
Abstract Background Women in the postpartum period are at greater risk of intimate partner violence (IPV), which may cause physical, sexual, or psychological harm and have a long-lasting negative impact on mother and child. Seeking help in case of IPV in the postpartum period can be difficult. Objective The purpose of this study was to examine service preferences among postpartum women in Germany (non-)affected by IPV. Methods In the cross-sectional study INVITE, postpartum mothers (n = 3,509) were interviewed via telephone. Using the WHO-Violence Against Women Instrument (WHO-VAWI), women were divided into groups: non-affected women and women affected by psychological, physical, and/or sexual IPV. Using analyses of variance, group differences regarding preferred services and modes of service provision were assessed. Examined service domains were psychosocial services (e.g., women´s shelter or self-help groups), medical services (e.g., gynecologist or emergency room), and midwives. Modes of service provision included direct communication (e.g., in person or video conference) and indirect communication (e.g., chat or e-mail). Results People from the women's social environment (e.g., family, friends) and specialized IPV services, such as women's shelters, were the most preferred support. Regarding service categories, women who experienced any type of IPV rated all three service domains less likely to be used than non-affected women. Most preferred provision mode was “in person”. Women affected by physical and/or sexual IPV rated direct modes more negatively than non-affected women. However, there were no differences between (non-)affected women regarding indirect modes, such as e-mails or apps. Discussion The present results indicate that services were rated less likely to be used by postpartum women affected by IPV. Potential barriers which lead to these ratings need to be investigated. Efforts should be made to increase awareness of IPV and the beneficial effects of support.